INFLUENCE OF CATEGORY SYSTEM ON THE POSSIBILITIES TO PARTICIPATE IN A MEN'S JUNIOR WORLD CHAMPIONSHIPS IN HANDBALL - Gutiérrez Óscar; Saavedra Miguel; Fernández Juan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The criteria's used for the International Handball Federation for the selection of the participants of the World Championship in the lower categories is based on the players born two years consecutively in the same category, starting the cut in the people born in an even year. During two seasons, these participants stay in the same category, and when the two years finalize the whole group move up to the next category. The sample is of 384 handball players that competed in the last World Championships of their category. The variables registered were the year of birth. The study took into account if the players were born in an even or odd year. The differences between the portion of athletes born in an even year and an odd year were calculated with the binominal test contrasting the proportion of 50%. In the male junior categories more players were born in an even year than an odd year, with significant differences.